Is substance use of any substance? Study on substance use and mental health on Russian, Somali and Kurdish origin populations in Finland - Salama, Essi (fi=Turun yliopisto|en=University of Turku|, 2022)
To date, our knowledge on substance use in migrated populations in their host countries is scarce. In addition, associations between discrimination and substance use have been rarely investigated in the European context. The Finnish Migrant Health and Wellbeing Study (Maamu) collected information in 2010–2012 from Russian (n=526–688), Somali (n=338–472) and Kurdish (n=506–612) origin adults living in Finland using interviews and health examinations. For comparison, general population data were obtained from the national Health 2011 Survey (n=1,165). Alcohol use (AUDIT-C), daily tobacco smoking, lifetime cannabis use were used as outcomes. Substance use was examined in relation to contextual factors, including socio-demographic factors, migrationrelated factors, depressive and anxiety symptoms, potentially traumatic experiences, and perceived discrimination. Statistical analyses were performed using logistic regression and best-fitting models (Akaike’s Information Criteria, AIC). Compared with the general population, binge drinking was less prevalent among all migrant origin groups, while daily tobacco smoking was more prevalent among Russian and Kurdish origin men. Substance use associated with depressive and anxiety symptoms and suicidal ideation among the Kurdish origin population. Potentially traumatic experiences were associated with binge drinking among the Kurdish, and with lifetime cannabis use among Russian origin population. Perceived discrimination was associated with alcohol use and cannabis use only among the Kurdish origin population. In conclusion, substance use occurred in all the studied migrant origin groups but the patterns of substance use and associations to contextual factors were unique to each group. The findings of this thesis draw attention to mental health problems and traumatic experiences associating with substance use to which particularly forced migrants might be exposed. Perceived discrimination associating with substance use highlights its importance as a determinant of wellbeing among migrant origin populations.

Päihteiden käyttö ja mielenterveys Suomessa asuvien venäläis-, somali- ja kurditaustaisten keskuudessa Päihteiden käytöstä maahan muuttaneiden keskuudessa on rajoitetusti tutkimustietoa jopa Euroopan laajuudella. Erityisen vähän tiedetään päihteidenkäytön ja syrjinnän välisistä yhteyksistä maahanmuuttajataustaisen väestön keskuudessa. Vuosina 2010–2012 toteutetussa Maahanmuuttajien terveys- ja hyvinvointitutkimuksessa (Maamu) kerättiin tietoa Suomessa asuvista venäläis- (n=526–688), somali- (n=338–472) ja kurditaustaisista (n=506–612) aikuisista haastattelujen ja terveystarkastusten avulla. Suomessa asuvasta yleisväestöstä koostuvan verrokkiryhmän tiedot on poimittu Terveys 2011 tutkimuksen aineistosta (n=1,165). Alkoholin käyttö (AUDIT-C), päivittäinen tupakointi ja elinaikainen kannabiksen käyttö olivat tutkimuksen päätemuuttujia. Päihteidenkäyttöön liittyvinä selittävinä tekijöinä tarkasteltiin sosiodemografisia muuttujia, maahanmuuttotaustaan liittyviä muuttujia, masennus- ja ahdistusoireita, traumakokemuksia ja koettua syrjintää. Tilastolliset analyysit tehtiin logistista regressiota käyttäen ja malleja tarkasteltiin Akaiken informaatiokriteeriä käyttäen. Yleisväestöön verrattuna humalahakuinen alkoholinkäyttö oli harvinaisempaa kaikissa tutkituissa maahanmuuttajataustaisissa ryhmissä. Päivittäinen tupakointi oli venäläis- ja kurditaustaisilla miehillä yleisempää kuin yleisväestössä. Päihteidenkäyttö oli yhteydessä masennus- ja ahdistuneisuusoireisiin sekä itsetuhoisiin ajatuksiin kurditaustaisten keskuudessa. Traumakokemukset olivat yhteydessä humalahakuiseen alkoholinkäyttöön kurditaustaisilla ja elinaikaiseen kannabiksen käyttöön venäläistaustaisilla. Koettu syrjintä oli yhteydessä alkoholinkäyttöön ja elinaikaiseen kannabiksen käyttöön vain kurditaustaisten keskuudessa. Tutkimustulokset korostavat päihteidenkäytön yhteyksiä mielenterveyden ongelmiin ja traumaattisiin kokemuksiin, joita erityisesti humanitäärisistä syistä maahan muuttaneet saattavat kokea. Koetun syrjinnän ja päihteidenkäytön yhteys osoittaa, että syrjintä on merkittävä terveyteen ja hyvinvointiin vaikuttava tekijä maahan muuttaneiden väestönosien keskuudessa.